Diversity of thysanoptera in chrysanthemum [dendranthema grandiflorum (ramat.) Kitamura] var. Harman in Texcoco, state of Mexico - Loera-Alvarado, Esperanza; Ortega-Arenas, Laura Delia; Johansen-Naime, Roberto Miguel; González-Hernández, Héctor; Lomelí-Flores, Refugio; Santillán-Galicia, Ma. Teresa; Ochoa-Martínez, Daniel Leobardo (Instituto de Ecología, A.C., 2017)
In order to determine the diversity of thrips species associated with Chrysanthemum [Dendranthema grandiflorum (Ramat.) Kitamura] var. Harman, at four locations in the municipality of Texcoco, State of Mexico, larvae and adults were collected biweekly in the periods from March to June and August to November 2011. The collected individuals were subjected to clarification techniques and mounted for identification. Seventeen species of thrips were identified, included in the genera Frankliniella with 13 species and Anaphothrips, Chrirothrips, Neohydatothrips and Leptothrips with one species each. Most abundant species were F. occidentalis and F. brunnescens (88.6%). The diversity and abundance of thrips was similar in the four localities. The ecological relevance of our findings is discussed